Newspaper cuttings collected by Florence O'Donoghue with typescript extracts from the 'Cork Examiner', - O'Donoghue, Florence, 1895-1967 (1917)
Cuttings relate to the history of the I.R.A. and its members, independence movements in Cork and Kerry and various commemorations.